Observation of the Z$→ψ\ell^+\ell^-$ decay in pp collisions at $\sqrt{s}=$ 13 TeV - CMS collaboration (2298 authors) (2018)
This Letter presents the observation of the rare Z boson decay Z $→ψ\ell^+\ell^-$. Here, $ψ$ represents contributions from direct J/$ψ$ and $ψ$(2S) $→$ J/$ψ X$, $\ell^+\ell^-$ is a pair of electrons or muons, and the J/$ψ$ meson is detected via its decay to $μ^+μ^-$. The sample of proton-proton collision data, collected by the CMS experiment at the LHC at a center-of-mass energy of 13 TeV, corresponds to an integrated luminosity of 35.9 fb$^{-1}$. The signal is observed with a significance in excess of 5 standard deviations. After subtraction of the $ψ$(2S) $→$ J/$ψ X$ contribution, the ratio of the branching fraction of the exclusive decay Z $→ψ\ell^+\ell^-$ to the decay Z $→μ^+μ^-μ^+μ^-$ within a fiducial phase space is measured to be $\mathcal{B}($Z $→ψ\ell^+\ell^-) / \mathcal{B}($Z $→μ^+μ^-μ^+μ^-) =$ 0.67 $±$ 0.18 (stat) $±$ 0.05 (syst).